Response of Nutritional Biomarkers in Bangladeshi Subjects Given an Immunological Challenge (P10-096-19) - Craft, Neal (Curr Dev Nutr, 2019)
OBJECTIVES: Unreliability of nutritional biomarkers (NB) have been reported in apparently healthy people with subclinical inflammation. The objective of this study was to measure NBs before and after a vaccination induced inflammation. NBs included: Ferritin (Fer), soluble Transferrin Receptor (sTfR), Retinol Binding Protein 4 (RBP4), Thyroglobulin (Tg), 25OH-Vitamin D(3) (25OH-D), retinol (VA), Folates, Cobalamins (B12), and inflammatory markers, acid 1- α-Glycoprotein (AGP) and C-Reactive Protein (CRP). METHODS: Children aged 12–18 months were recruited at ICDDR-B in Dhaka, Bangladesh. Blood samples were drawn initially and 1 day post inoculation with Pentavalent vaccine. Harvested serum was frozen and transported to labs for analysis. Fer, sTfR, RBP4, Tg, AGP, and CRP, were measured in 96-well format by chemiluminescent with the Quansys Human Micronutrient 7 Plex array and the Q-view reader. Serum Folates and Total B12 were estimated microbiologically using ALPCO-Immundiagnostik 96-well kits. Serum 25OH-D and VA were measured by LC-MS/MS. RESULTS: Vaccine induced inflammation significantly increased CRP, AGP, Fer and sTFR by 4.48 mg/L (798%), 0.435 g/L (48%), 9.57 µg/L (60%) and 7.6 mg/L (31%), respectively. Furthermore, inflammation significantly reduced VA, RBP4, and B12 by 74.7 µg/L (18%), 0.637 mmol/L (34%), and 38.74 ng/L (14%), respectively. Tg, Folates and 25OH-D were not significantly affected by the vaccine induced inflammatory response. CONCLUSIONS: The study confirms that mild inflammation significantly alters the reliability of 7 out of 10 measured nutritional biomarkers after vaccine inoculation. The measurement of inflammatory markers is necessary for accurate determination of nutritional status in young children. FUNDING SOURCES: Funding provided by the Bill and Melinda Gates Foundation.